(untitled) (Annual of the Faculty of Philosophy in Skopje, 2024)
This article explores how peace studies deal with two interrelated issues: nuclearism and militarism. Nuclearism assumes the practice of spreading nuclear threats along with the security thinking and power structures that surround the doomsday weapons. Militarism is about the deeply embedded belief that military power (including the nuclear one) is the only way to preserve one’s national security. In short, today’s world deals not only with stockpiles of existing weapons but also with the way of thinking about their use, reduction or abolition. The general hypothesis is that the academic and intellectual efforts invested in these issues are (self) limited and developed in a climate of self-censorship and organized hypocrisy. This makes them not only ineffective but also prone to the preservation of the global status quo as the best solution for peace in the world. Scientists are involved in the technical aspects of the weapons management. But scholars from the social sciences and humanities (i.e. where the peace researchers mostly come from) are expected to deal with the deconstruction of the dominant way of thinking (both in academia and out of it) and promotion of the idea that a different world is possible. Or the alternative is nuclear holocaust.